Simulation study of a tree similarity measure based on small subtree counts - Bloznelis, Mindaugas; Radavičius, Irmantas (Lietuvos matematikos rinkinys, 2009)
Augsten, Böhlen and Gamper [1] suggested a measure of similarity between ordered and labeled trees based on subtree counts: two trees are declared close if they contain similar number of copies of ordered and labeled subtrees of a given form, called pq-gram. We report the results of a simulation study of statistical properties of distances based on pq-grams.